Quasi-free goods and social norms: The effects of quantity restrictions and scrutiny - Shlomi Boshi; Moshik Lavie; Avi Weiss (Bar-Ilan University, Department of Economics, 2014)
In this paper we consider the effect of quantity restrictions and scrutiny on the consumption of quasi-free goods. A good is quasi-free if it is zero priced, but it is consumed in the context of a social setting (e.g., as an employee, client, friend, etc.). Examples include cookies at a picnic, candies in a doctor's office, and perks offered to workers such as free soft drinks. Casual observation, including initial experience with unlimited vacation policies by some major companies (Evernote, IBM, Bestbuy), suggests that placing limitations on consumption can lead to an increase in the level of consumption of such goods, while removing existing limitations (as in the case of vacations) may result in a decrease in consumption. We attribute this to the consumer's perceptions about the social norm and how this perception is affected by the presence of a quantity restriction. In this paper we develop a simple model of quasi-free goods consumption showing the effect of a quantity restriction and of observability of the consumer's actions, and then test the model in a field experiment. The results clearly show that allowing unlimited consumption leads to less consumption, however, such behavior all but disappears when the subjects' choices are unobserved, including by the experimenter. This suggests that consumers are more concerned with how they are perceived by others than with self-image concerns.
Keywords: 330; Geschenk; Konsum; Ökonomisches Prinzip; Soziale Norm; Feldforschung